Ultraviolet resistance and other physical properties of softwood polymer nanocomposites reinforced with ZnO nanoparticles and nanoclay. Issue 1 (1st January 2017) - Hazarika, Ankita; Maji, Tarun K.
Abstract: Wood polymer nanocomposites (WPNCs) based on nano-ZnO and nanoclay were prepared by impregnation of melamine formaldehyde–furfuryl alcohol copolymer, 1, 3-dimethylol-4, 5-dihydroxyethyleneurea (DMDHEU), a cross-linking agent and a renewable polymer obtained as a gum from the plant Moringa oleifera under vacuum condition. Fourier transform infrared spectroscopy (FTIR) and X-ray diffractometry (XRD) studies were employed for the characterization of modified ZnO and WPNCs. The change in crystallinity index (CrI) value of the cellulose in wood and the distribution of ZnO nanoparticles in composites were determined using FTIR and XRD. Scanning electron microscopy and Transmission electron microscopy showed the presence of nanoparticles and nanoclay in the cell lumen or cell wall of wood. An enhanced UV resistance property was shown by the treated wood samples as judged by lower weight loss, carbonyl index, lignin index, cellulose CrI values, and mechanical property loss compared to the untreated wood samples. Wood polymer composites treated with 3 phr each of nanoclay, ZnO, and the plant gum showed an improvement in mechanical properties, flame-retarding properties, thermal stability, and lower water uptake capacity.